Mollie Katzen's vegetable heaven - Katzen, Mollie (New York Hyperion, 1997)
"This companion volume to the 26-part public television series which begins airing in October 1997 contains more than 200 recipes for delicious and surprising fare and is illustrated with more than 25 of Katzen's luminous paintings, richly evocative of the pleasures of cooking and eating"--Provided by publisher.
Keywords: Cooking (Vegetables)